XIX ӘСИРДИҢ АҚЫРЫ XX ӘСИР БАСЛАРЫНДА ҚАРАҚАЛПАҚСТАНДАҒЫ МӘДЕНИЙ-ТАРИЙХЫЙ ШАРАЯТ ҲӘМ ЖӘДИДШИЛИК АҒАРТЫЎШЫЛЫҚ ҲӘРЕКЕТИ - Сейтмуратов, Қ. (FAN va JAMIYAT, 2024)
The article examines the cultural and historical conditions of Karakalpakstan in the second half of the 19th - early 20th centuries, the emergence of the Jadid movement, reforms in the field of education, the creation of Jadid schools, and the publication of new generation textbooks.